2007
DOI: 10.1109/led.2007.896904
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Ion Implantation Isolation Planar Process for AlGaN/GaN HEMTs

Abstract: Abstract-A multienergy oxygen ion implantation process was demonstrated to be compatible with the processing of highpower microwave AlGaN/GaN high electron mobility transistors (HEMTs). HEMTs that are isolated by this process exhibited gate-lag-and drain-lag-free operation. A maximum output power density of 5.3 W/mm at V gs = −4 V and V ds = 50 V and a maximum power added efficiency of 51.5% at V gs = −4 V and V ds = 30 V at 3 GHz were demonstrated on HEMTs without field plates on sapphire substrate. This isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…2 Several investigations have been conducted for the basic mechanisms of gate leakage current, 4-10 and leakage current reduction. 11 Zhang et al 7 analyzed the leakage current mechanisms in the Schottky contacts of both n-GaN and AlGaN/GaN at different temperatures and concluded that tunneling current dominates at temperatures below 150 K, whereas the Frenkel-Poole emission dominates at temperatures higher than 250 K. Miller et al 8 have shown that the reverse-bias leakage in AlGaN/GaN can be analyzed in a conventional tunneling model. The effects of the dislocations and defects states, in the reverse-bias leakage, have been suggested by several studies for GaN and Al x Ga 1−x N heterostructures 4,6,7 wherein defects, in particular dislocations, might play an important role in reverse-bias leakage.…”
mentioning
confidence: 99%
“…2 Several investigations have been conducted for the basic mechanisms of gate leakage current, 4-10 and leakage current reduction. 11 Zhang et al 7 analyzed the leakage current mechanisms in the Schottky contacts of both n-GaN and AlGaN/GaN at different temperatures and concluded that tunneling current dominates at temperatures below 150 K, whereas the Frenkel-Poole emission dominates at temperatures higher than 250 K. Miller et al 8 have shown that the reverse-bias leakage in AlGaN/GaN can be analyzed in a conventional tunneling model. The effects of the dislocations and defects states, in the reverse-bias leakage, have been suggested by several studies for GaN and Al x Ga 1−x N heterostructures 4,6,7 wherein defects, in particular dislocations, might play an important role in reverse-bias leakage.…”
mentioning
confidence: 99%
“…Doing the analysis in Section IV using the results from [7], where the devices withstood a gate current of 900 mA/mm and voltage of 3.5 V without severe degradation, would result in an optimal bias resistance of 30 Ω • mm, giving a maximum input power of 43 dBm for a 2 × 50 μm device. Minimization of mesa leakage or use of other methods such as ion implantation, which can provide device isolation without the formation of a mesa where the GaN channel is in contact with the gate metal [14], could thus be essential for robust LNA design.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, we obtained high-quality nitride layers grown by metalorganic vapor phase epitaxy (MOVPE). The undoped GaN shows resistance higher than 100 k ohm/sheet and AlGaN/GaN heterostructure shows high electron mobility of 1760 cm 2 /V, meaning that these characteristics are favorable especially for an AlGaN/ GaN heterostructure field effect transistor [6]. In addition to the growth of such a high quality nitride layer, the growth process using this AlON buffer layer reduces the growth time and the number of the growth parameters compared with the two step growth using a LT buffer layer.…”
Section: Introductionmentioning
confidence: 99%